Some Residues and Contaminants in Milk and Dairy Products - COLAK, HILAL; HAMPIKYAN, HAMPARSUN; BARIS BINGOL, ENVER (Asian Journal of Chemistry, 2010)
Milk and dairy products are important components of the human diet. Some residue and contaminants in milk and dairy products can be classified as antibiotics, mycotoxins, anthelmintics, pesticides, dioxins, hormones and heavy metals. Presence of the residual concentrations of these compounds in milk and dairy products can be an important direct indicator for the quality status of the milk and their products, because these agents can easily transported to milk and dairy products which are evaluated the most important contamination sources for the human health. In this review, some residue and contaminants and surveys on this subject in Turkey were considered.